USM LOOKS AT OWLS AS BIOLOGICAL AGENTS FOR PEST CONTROL OF MICE, CONSERVATION AND RICHNESS IN BIODIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 20 January 2016 – Researchers at Universiti Sains Malaysia (USM) are actively looking at the capabilities of owls (Tyto alba javanica) for the purpose of pest control such as mice, and also for conservation activities as well as increasing the biological diversity in urban and farming areas throughout Malaysia, including at the USM Main Campus.